Derivational Valency and Potential of Combining Forms in Present-Day English Word-Building - Alanakyan, Aida (Armenian Folia Anglistika, 2006)
Linguistic units known as “combining forms” are of great interest in terms of the word-building efficiency. The research aims to specify the place and role of the combining forms in word-formation process of English. The investigation is conducted on the dictionary data of neologisms. The derivational, morphological, distributional, functional analyses of the material allow to identify the differences among combining forms and hence, the factors conditioning the degree of efficiency of certain units. The initial findings, though with some reservations, confirm the hypothesis that the percentage of compounding in the system of English word-formation is considerably increasing at the expense of non-patterned derivational methods.